Multiple carpometacarpal dislocations and an associated fracture of the hamate: an uncommon injury - Brinkman, Jacobus Nicolaas (BMJ Case Rep, 2016)
Dislocation of the four ulnar carpometacarpal (CMC) joints with a concurrent fracture of the hamate is a rare injury, with a paucity of published cases. A great force is required to dislocate a CMC joint. Diagnosis can easily be missed, due to other serious associated injuries. Appropriate treatment of CMC joint dislocations usually leads to excellent outcomes. We present a case of dorsal dislocation of the four ulnar CMC joints after punching a wall. The injury was treated with a closed reduction and percutaneous transfixation with Kirschner-wires. Despite the extensive injury, the functional result was good (full and painless range of motion) at 12 weeks of follow-up.